A Literature Review on the Imidazole - Shallal, Muhammed Abdel Hasan (American International Journal of Multidisciplinary Scientific Research, 2019)
This review gives some information about imidazole ring as a ( ligand , complex , antimicrobial , antimalarial , anticancer , uses , applications , linked with active groups such as Schiff base , azo group , ..).